The Effect of Pounding Tool and Length of Time of Pounding on the Quality of Brown Rice Flour (Oryza Nivara) - Ardiansyah Dwi Wicaksono Ardiansyah; Al Machfudz; Lukman Hudi; Ida Agustini Saidi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of the pounder and the duration of pounding on the quality of brown rice flour. This research using a factorial randomized block design. The first factor is pounding with wooden mortar and stone mortar, while the second factor is pounding with 3 levels, namely 20, 30 and 40 minutes. Statistical analysis using ANOVA and further test using 5% BNJ test. Organoleptic test was analyzed using Friedman test. The results showed that there was an interaction between the type of pounder used and the duration of pounding on the percentage of particle size, color organoleptic value, aroma organoleptic value and organoleptic value of brown rice flour texture but had no significant effect on water content, fat content, and crude fiber content of brown rice flour. . Treatment with a masher (stone mortar) with a pounding time of 40 minutes had a very significant effect on the number of mesh 80 passes in brown rice flour. The organoleptic test was on the highest color with a value of 3.75 (slightly dark red) with a wooden mortar pounding treatment and 20 minutes of pounding time, the highest aroma organoleptic test with a value of 3.075 (rather typical of brown rice) with a stone mortar pounding treatment and 30 minutes of pounding time, and the highest value organoleptic texture was 3.55 (smooth) with stone mortar pounding treatment and 30 minutes of pounding time.